Interactive technology use and child development: A systematic review. - Arabiat, Diana; Al Jabery, Mohammad; Robinson, Sue; Whitehead, Lisa; Mörelius, Evalotte (Child: Care, Health & Development, 2023)
Background: There is mixed evidence regarding the impact of interactive digital devices on child development. Tentatively some studies suggested that the use of digital devices may correlate negatively with language, executive function, and motor skills. However, attempts to amalgamate this evidence has been limited related to the available number of experimental and cohort studies that have evaluated the impact of digital technology use on child development. We conducted this review to determine the impact of interactive digital devices on child development among children aged 7 years or younger. Interactive technology has been defined as methods, tools, or devices that users interact with in order to achieve specific tasks. Data source: To carry out this systematic review, databases CINAHL, MEDLINE, Embase, PsychINFO, Scopus and Google Scholar were searched for relevant studies. Study selection: We used the Joanna Briggs Institute methodology for systematic reviews. Data extraction: Data extraction and synthesis was carried out by two reviewers and checked by a third reviewer. Studies were stratified into tiers depending on the level of evidence provided and the domain of development assessed. Results: Fifty‐three studies were eligible for inclusion in the review, 39 Tier 1 (randomized controlled trials and quasi‐experimental studies) and 16 Tier 2 (descriptive studies). Children's use of interactive digital technology was positively associated with receptive language and executive function and negatively associated or unrelated to motor proficiency. Other critical aspects informing the evidence, such as dose of exposure, intensity, or duration, were inconsistently reported, making estimates of exposure tentative and imprecise. Conclusion: The studies included in this review were predominantly correlational or comparative in nature and focuses on cognitive domains of learning rather than a specific developmental outcome. It is difficult to generalize our findings beyond the digital devices or applications that have been evaluated by earlier studies. The contextual factors that may moderate the relationship require elaboration in future studies.